R and Its Applications on the Ecological Research - Sihaloho, Hendra Freddy (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2015)
The increase of research activities in recent years has generated a lot of data to be analysed. Research-related communities need a powerful software to perform their analyses. And, it can be a problem, particularly for those who live in developing countries, where their financial capability is low to buy the proprietary programs. R may provide the solution to this obstacle. Since it is an open source software, which can be installed on major operating systems. In addition, it is highly maintained by R Core Team, which ensures that the program and its packages work well on across platforms. The increase usage of R, especially in universities is not only a proof that the program can be relied on, but it is also a guarantee that the software will continue developing. R and its capability for ecological research activities particularly will be described on this short note